2022
DOI: 10.3390/ijms23063054
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower WRINKLED1 Plays a Key Role in Transcriptional Regulation of Oil Biosynthesis

Abstract: Sunflower (Helianthus annuus) is one of the most important oilseed crops worldwide. However, the transcriptional regulation underlying oil accumulation in sunflower is not fully understood. WRINKLED1 (WRI1) is an essential transcription factor governing oil accumulation in plant cells. Here, we identify and characterize a sunflower ortholog of WRI1 (HaWRI1), which is highly expressed in developing seeds. Transient production of HaWRI1 stimulated substantial oil accumulation in Nicotiana benthamiana leaves. Dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Consistent with this notion, AtWRI1 orthologs have been identified in various plant species, both monocots and dicots, such as Brassica napus, Brachypodium distachyon, Camelina sativa, Glycine max, Elaeis guineensis, Helianthus annuus, and Zea mays (11,(19)(20)(21)(22)(23)(24)(25)(26). Transgenic plants overexpressing AtWRI1 or WRI1 orthologs exhibit elevated seed oil accumulation (4,9,11,19,24,26,27). In addition, ectopic expression of AtWRI1 or WRI1 orthologs leads to increased oil accumulation in leaves of stable transgenic plants or tobacco plants (via transient expression) (24,(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Consistent with this notion, AtWRI1 orthologs have been identified in various plant species, both monocots and dicots, such as Brassica napus, Brachypodium distachyon, Camelina sativa, Glycine max, Elaeis guineensis, Helianthus annuus, and Zea mays (11,(19)(20)(21)(22)(23)(24)(25)(26). Transgenic plants overexpressing AtWRI1 or WRI1 orthologs exhibit elevated seed oil accumulation (4,9,11,19,24,26,27). In addition, ectopic expression of AtWRI1 or WRI1 orthologs leads to increased oil accumulation in leaves of stable transgenic plants or tobacco plants (via transient expression) (24,(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 57%
“…WRI1 is therefore considered a key regulator in the transcriptional control of plant oil production (1,10). Consistent with this notion, AtWRI1 orthologs have been identified in various plant species, both monocots and dicots, such as Brassica napus, Brachypodium distachyon, Camelina sativa, Glycine max, Elaeis guineensis, Helianthus annuus, and Zea mays (11,(19)(20)(21)(22)(23)(24)(25)(26). Transgenic plants overexpressing AtWRI1 or WRI1 orthologs exhibit elevated seed oil accumulation (4,9,11,19,24,26,27).…”
Section: Introductionmentioning
confidence: 68%
“…CcWRI1A/B were preferentially expressed in the developing embryo (Figure 2C,D), which is similar to those of AtWRI1, GmWRI1s, and HaWRI1. 2,7,20 Previous studies have shown that GmWRI1A and GmWRI1B were both nucleus-located, while only GmWRI1A but not GmWRI1B can transactivate targeted genes, suggesting that GmWRI1A and GmWRI1B are likely to regulate downstream genes in different ways. 20 It was also found that ZmWRI1B was developing into a housekeeping gene to maintain the TAG biosynthesis involved in different cellular processes; nonetheless, ZmWRI1A still mainly contributed to promoting FA biosynthesis during grain filling.…”
Section: Ccwri1a/b Can Directly Combine With and Activate The Promote...mentioning
confidence: 99%
“…It is the major source of carbon and energy for seed germination and seedling establishment. It is also applied as a major calorie source for human nutrition and plays a critical role in industrial manufacturing. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation